Validation of a lower limb muscle model by using volleyball block preparation movement - Wang, I. L.; Gao, J. J.; Gu, C. Y.; Chen, W. C. (14th International Symposium on 3D Analysis of Human Movement, 2016)
The purpose of this study was to simulating the lower limb muscle action performed and validated the musculoskeletal model. One elite female volleyball player volunteered to participated this study. Anybody Modeling System (AMS) software were used to evaluate lower limb muscle action during the blocking motion in volleyball. The data validated with nine surface electromyography. The results show that biceps femoris, rectus femoris, vastus lateralis, vastus medialis, and the lateralis and vastus head of the gastrocnemius were similar. The semitendinosus, semimembranosus, and tibialis anterior were differences. The results show that muscle simulation signals pattern was similar to SEMG values in the biceps femoris, rectus femoris, vastus lateralis, vastus medialis, and the lateralis and vastus head of the gastrocnemius. The differences pattern were observed in the semitendinosus, semimembranosus, and tibialis anterior. Slight differences in muscle simulation values and SEMG values were observed in the preparation movement for blocking.